Cohesiveness and Emotional Intelligence as Predictors of Clinical Performance among Staff Nurses in a Tertiary Hospital - Renasha Firda Hanannisa; Sri Suwarsi; Maya Tejasari (STIE Amkop Makassar, 2026)
Purpose: This study examines whether team cohesiveness and emotional intelligence significantly predict the clinical performance of inpatient nurses.Research Design and Methodology: A quantitative cross-sectional survey was conducted among 197 staff nurses in a tertiary referral hospital in Bandung, Indonesia. Data were collected using structured questionnaires measuring cohesiveness, emotional intelligence, and performance. Instrument validity and reliability were confirmed, followed by classical assumption testing and multiple linear regression analysis, including t-tests, F-tests, and coefficient of determination.Findings and Discussion: Both cohesiveness and emotional intelligence were rated high by respondents and showed positive and significant effects on nurse performance, both partially and simultaneously. The model explained 36.2% of the variance in performance, indicating that interpersonal and emotional competencies are meaningful but not exclusive determinants of clinical outcomes.Implications: Strengthening teamwork climate and emotional competence development programs may improve nursing performance. Hospital management should integrate team-based training and emotional intelligence development into workforce policies, while future studies should incorporate organizational and leadership variables to increase explanatory power.